Aplikasi Limbah Daun Trembesi (Samanea saman Jacq Merr) Sebagai Pupuk Hijau Terhadap Pertumbuhan Tanaman Bunga Matahari (Helianthus anuus L.): Effect of Applying of Rain Tree Leaf (Samanea saman Jacq Merr) as Green Manure on The Growth of Sunflower (Helianthus anuus L.) - budi, budi utomo; Utomo, Budi; Purwanti, Sri (Journal of Applied Plant Technology, 2023)
The rain tree (Samanea saman) has the potential to become a green manure material for soil fertilizer due to its high biomass production and air N2 fixation ability. The research aims to determine the possibility of rain tree leaf waste being used as organic fertilizer in the construction of city parks without having to go through the previous composting process. The experiment was in polybags with four treatments namely (1) control with pure soil media, (2) addition of 20% volume of trembesi leaves composted, (3) adding 20% ​​volume of cocopeat growing media, and (4) adding 20% ​​volume of fresh rain tree leaves without composting. Experiment using sunflower plants as a representation of ornamental plants in the construction of city parks. The results showed that the application of composted rain tree leaves had the best effect on the growth and generative performance of sunflower plants compared to the application of fresh rain tree leaves without composting, comparison of cocopeat growing media and controls of pure soil media. The research findings will strengthen the recommendation that the application of organic matter to the soil should be through a composting or decomposition process first.